Thiol antioxidant-functionalized CdSe/ZnS quantum dots: Synthesis, Characterization, Cytotoxicity - Zheng, Hong (J Biomed Nanotechnol, 2013)
Nanotechnology is a growing industry with wide ranging applications in consumer product and technology development. In the biomedical field, nanoparticles are finding increasing use as imaging agents for biomolecular labeling and tumor targeting. The nanoparticle physiochemical properties must be tailored for the specific application but chemical and physical stability in the biological milieu (no oxidation, aggregation, agglomeration or toxicity) are often required. Nanoparticles used for biomolecular fluorescent imaging should also have high quantum yield (QY). The aim of this paper is to examine the QY, stability, and cell toxicity of a series of positive, negative and neutral surface charge quantum dot (QD) nanoparticles. Simple protocols are described to prepare water soluble QDs by modifying the surface with thiol containing antioxidant ligands and polymers keeping the QD core/shell composition constant. The ligands used to produce negatively charged QDs include glutathione (GSH), N-acetyl-L-cysteine (NAC), dihydrolipoic acid (DHLA), tiopronin (TP), bucilliamine (BUC), and mercaptosuccinic acid (MSA). Ligands used to produce positively charged QDs include cysteamine (CYS) and polyethylenimine (PEI). Dithiothreitol (DTT) was used to produce neutral charged QDs. Commercially available nonaqueous octadecylamine (ODA) capped QDs served as the starting material. Our results suggest that QD uptake and cytotoxicity are both dependent on surface ligand coating composition. The negative charged GSH coated QDs show superior performance exhibiting low cytotoxicity, high stability, high QY and therefore are best suited for bioimaging applications. PEI coated QD also show superior performance exhibiting high QY and stability. However, they are considerably more cytotoxic due to their high positive charge which is an advantageous property that can be exploited for gene transfection and/or tumor targeting applications. The synthetic procedures described are straightforward and can be easily adapted in most laboratory settings.